Pengaruh Penggunaan Pusat Sumber Perpustakaan Sekolah di Sekolah-Sekolah Menengah Daerah Kota Bharu, Kelantan Darul Naim - Wan Zakaria, Haji Wan Ismail (1996)
This study attempts to investigate the influence in the usage of the school library resource centres in secondary schools in Kota Bharu District, Kelantan Darulnaim. This study involves five schools. The influence in the usage of school library resource centre is related to the factors which attract people to go to library. This factors are demographic factors, physical facilities, collections and arrangement, staff and service as well as the material and financial contributions. The objective of the study also involves the influence of the independent variable factors on the usage of school library. 400 sets of questionnaires are distributed to the respondents which comprises form four students from five schools. These selected schools consist of boys and girls’ schools, mixed schools, agama schools and Chinese medium schools 80 students and two teachers in charge of library take part in this study. The respondents consists of 360 students and 10 teachers. The data obtained from the information will be analysed by using descriptive statistics, t-test, One Way ANOVA, correlation coefficients, multiple regression and as well as qualitative analysis.